ASSOCIATION BETWEEN MATERNAL ANEMIA AND LOW BIRTH WEIGHT AMONG NEWBORNS AT A TERTIARY CARE HOSPITAL (The Research of Medical Science Review, 2025)
Background: Maternal anemia is a prevalent health issue, often linked to low birth weight (LBW) in newborns. Some studies show a higher incidence of LBW among anemic mothers, others report insignificant difference. To resolve these inconsistencies, this study was conducted at a tertiary care hospital to explore the association between maternal anemia and LBW, accounting for various factors. Objective: To determine association between maternal anemia and low birth weight among newborns at a tertiary care hospital. Duration: Six months. Methodology: After approval from the hospital's Ethical Review Committee, 100 pregnant women presenting at the Department of Obstetrics & Gynaecology, Combined Military Hospital (CMH), Sialkot, were enrolled in the study after informed consent. Hemoglobin levels were checked, and participants were divided into two groups: cases (anemic women) and controls (non-anemic women). They were followed until birth, with newborns classified as LBW based on the operational definition. Findings were provided by a senior consultant, and the resident recorded them to avoid bias. Confounding variables were controlled through exclusion, and treatment for anemic mothers and LBW infants followed department protocols. Results: The study included 100 women with a mean maternal age of 28.18 ± 5.13 years, 62% aged 18-30, and 38% aged 31-40. The mean gestational age at delivery was 38.72 ± 1.22 weeks, with 71% delivered at 37 to 39 weeks. The mean BMI was 25.60 ± 3.97 kg/m², 60% classified were overweight. The mean number of previous pregnancies was 2.43 ± 1.03, 58% were having two or fewer children. Sixty-two percent lived in rural areas, and 56% of the newborns were boys. The baseline characteristics of the anemic and non-anemic groups were similar (p > 0.05). Among women with anemia, 68% had low birth weight (LBW) infants, compared to 40% in the non-anemic group, statistically significance of (p = 0.005). The odds ratio (OR) for LBW was 3.188 (95% CI: 1.403–7.241) in the anemic group indicating a threefold increased risk. Conclusion: In conclusion, this study demonstrates that the women with anemia are more than three times at risk to deliver LBW infants compared to those without anemia. These findings emphasize the importance of addressing maternal anemia during pregnancy to reduce the risk of adverse outcomes.